Gangguan Spektrum Autisme pada Anak: Analisis dan Visualisasi Bibliometrik pada Database Scopus - Mashadi, Aisya; Nursalim, Mochamad; Purwoko, Budi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This study is motivated by the limited research on [investigations addressing global trends and research patterns, despite the significant impact of this phenomenon on various scientific fields, including health, education, and child developmental psychology. The study aims to analyze and visualize scholarly publications related to Autism Spectrum Disorder in children indexed in the Scopus database during the period of 2020 to 2024 using a bibliometric approach. This study employed a quantitative descriptive method through bibliometric analysis. Data were collected by searching documents in the Scopus database using the keywords “Autism Spectrum Disorder” and “Children,” and analyzed using VOSviewer software to identify publication trends, citation trends, and popular keywords. The findings reveal a significant decline in the number of publications. The most prominent keywords identified were autism, child, mental health, intellectual disability, technology, and childhood. The study concludes that research on Autism Spectrum Disorder in children has experienced a sharp decline, particularly in the years 2023 and 2024. The implications of this research is the need to expand international collaboration to develop more inclusive approaches. Additionally, this study identifies future research opportunities on Autism Spectrum Disorder in children.